Implementation of Interactive E-Student Worksheets Based on Scaffolding to Enhance Collaboration Skills and Science Process Skills - Teuku Muhammad Alfatdri; Rini Safitri; Susilawati Susilawati; Muhammad Aditya Hidayah (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Collaboration skills and science process skills (SPS) are essential 21st-century competencies that remain low in science learning, thus requiring innovation in digital-based learning media capable of facilitating the integrated development of both skills. This study aims to implement and examine the effect of scaffolding-based interactive e-student worksheets on improving students' collaboration skills and SPS in the topic of energy. The research method used was a quasi-experiment with a nonequivalent control group design. The research sample consisted of 60 eighth-grade students of SMP Muhammadiyah 1 Banda Aceh, divided into an experimental class (n=30) that used scaffolding-based interactive interactive e-student worksheets and a control class (n=30) that used conventional worksheets. The research instruments included SPS test questions and a collaboration skills questionnaire. The results showed that the implementation of scaffolding-based interactive interactive e-student worksheets had a significant effect on improving collaboration skills, with an average N-Gain of the experimental class of 0.73, which is higher than that of the control class at 0.41. There was a significant improvement in the SPS of the experimental class students, with an average N-Gain of 0.70 in the high category, outperforming the control class at 0.61. Hypothesis testing using the independent sample t-test showed a significance value of p < 0.05 for both variables, indicating a significant difference between the experimental and control classes. This proves that scaffolding-based interactive interactive e-student worksheets are effective in improving students' collaboration skills and SPS, and are therefore recommended as an innovative learning medium in science education